Inverse Association Between Omega-3 Index and Severity of Covid-19: A Case–Control Study - Barra-Pezo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Background: Omega-3 fatty acids enhance immune response and modulate inflammation. This study aimed to determine the relationship between omega-3 fatty acid status and the severity of SARS-CoV-2 infection. Methods: Using a case–control design, we compared hospitalized patients with severe SARS-CoV-2 infection (cases, n = 73) with a group of ambulatory patients with mild SARS-CoV-2 infection (controls, n = 71). No patients were vaccinated against SARS-CoV-2. Results: The cases were older (p = 0.003), less educated (p = 0.001), had larger neck and smaller waist circumferences (p = 0.035 and p = 0.003, respectively), more frequently had diabetes (p < 0.001), consumed less fish (p < 0.001), consumed higher proportions of fried fish (p = 0.001), and had lower Omega-3 Index (O3I) values (p = 0.001) than controls. Cases had significantly lower rates of upper airway symptoms than controls. Lower O3I was associated with an increased likelihood of developing severe COVID-19 after adjusting for potential confounders (OR: 0.52; CI 0.32–0.86). Diabetes (OR: 4.41; CI 1.60–12.12), neck circumference (OR: 1.12; CI 1.03–1.21), and older age (OR: 1.03; CI 1.002–1.062) were also linked to COVID-19 severity. Fried fish consumption and low educational level were independent risk factors for severe COVID-19. Conclusions: This study suggests incorporating nutritional interventions to improve omega-3 status within nonpharmacological measures may help to reduce the severity of COVID-19. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.